PERKEMBANGAN INTELEKTUAL PADA ANAK SD NEGERI - Simamora, Anggi Putri; Ramadhani, Anisa; Pratiwi, Dewi; Manullang, Hanna Mawarni; Nafisa, Katri; Fadilla, Raudatul (Universitas Negeri Medan, 2023)
Elementary school students are children who are still in the intellectual development stage. Intellectual/cognitive is an aspect that must be developed in children. For that, parents and teachers need to understand this aspect of intellectual development. The purpose of writing this article is to examine the intellectual development of elementary school students. This type of research is qualitative research using a literature study design. The findings prove that Every elementary school child will definitely experience intellectual development. Development The intellectual level of elementary school children at the concrete operational stage is around the age of 7 years around 11-12 years old, according to the age of elementary school children. So that we know developments elementary school children, we can find out the characteristics of children's intellectual development based on concrete operational stages. So, by knowing the characteristics of development elementary school students, teachers and parents can know to what extent intellectual development that a school student should or has not gone through basic knowledge and know and can minimize the impact of problems on development child intellectual. and able to provide appropriate assistance efforts. Keywords: Development, Intellectual, Elementary School.